2017
DOI: 10.1101/191825
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Natural selection on plasticity of thermal traits in a highly seasonal environment

Abstract: This preprint has been reviewed and recommended by Peer Community In Evolutionary Biology (http://dx.doi.org/10.24072/pci.evolbiol.100048). For ectothermic species with broad geographical distributions, latitudinal/altitudinal variation in environmental temperatures (averages and extremes) are expected to shape the evolution of physiological tolerances and the acclimation capacity (i.e., degree of phenotypic plasticity) of natural populations. This can create geographical gradients of selection in which enviro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Empirical studies have shown that physiological adaptation during acclimation usually leads to environmental specialists (Bacigalupe et al, ; Levins, ). Species perform better in the specific environmental niche to which they were acclimated as compared to their ancestors, but their fitness is not changed or even reduced in other environmental niches to which they were not acclimated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical studies have shown that physiological adaptation during acclimation usually leads to environmental specialists (Bacigalupe et al, ; Levins, ). Species perform better in the specific environmental niche to which they were acclimated as compared to their ancestors, but their fitness is not changed or even reduced in other environmental niches to which they were not acclimated.…”
Section: Discussionmentioning
confidence: 99%
“…The two adaptation processes are interconnected to provide an opportunity for the organism in question to survive, reproduce, and compete in new environments (Willmott et al, ). Many empirical studies of thermal adaptation have focused on the scales and patterns of physiological adaptation, that is, phenotypic plasticity (Bacigalupe et al, ; Chown, Addo‐Bediako, & Gaston, ; Garrett et al, ; Willmott et al, ). In contrast, evolutionary inferences on how fast genetic adaptation can occur and how such adaptations may affect biological interactions among traits are relatively limited, particularly in plant pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…There is less consensus on the adaptive direction of clinal genetic variation in body size-and to some extent growth rate-with temperature or seasonality (see "Discussion"; Abrams et al 1996;Hodkinson 2005;Dmitriew 2011;Keller et al 2013). Furthermore, we did not expect phenotypic plasticity in development or growth to vary adaptively along climate gradients because, apart from acclimation (Bacigalupe et al 2018), there is little evidence that temperature-induced plasticity in development or growth of ectotherms is adaptive (van der Have and de Jong 1996; Angilletta and Dunham 2003;Overgaard et al 2011). In summary, the pattern illustrated in figure 1 is expected for development rate, but for other traits and plasticities there is no clear prediction.…”
Section: Introductionmentioning
confidence: 87%
“…As both the strength and shape of selection are key elements that impact the speed at which populations can evolve, determining whether selection in nature targets plasticity itself is of paramount importance. This is particularly relevant if we want to understand how organisms respond to fluctuating environments and whether they will be able to adapt in the face of climate change [71].…”
Section: Plasticity As a 'Matthew Effect'mentioning
confidence: 99%